AKTIVITAS ANTIOKSIDAN SENYAWA FLAVONOID DARI KULIT BATANG LEGUNG (Vitex pinnate Tour ex Linn) DENGAN METODA TIOSIANAT - Nasution, Musyirna Rahmah; Syafril, Dasni; -, Yuharmen (Fakultas MIPA dan Kesehatan Universitas Muhammadiyah Riau, 2011)
Antioxidant are the compounds capable to inhibit free radical reactions in the human body.This research was aimed to identify the antioxidant potency of flavonoid compound of extract metanol of legung bark (Vitex pinnate Tour ex Linn) by using linoleic-tyocyanate methods.The result suggested, that isolated flavonoid of methanol extract was produced five fraction and most of fraction conducted antioxidant activity more less than Î±-tokoferol. But, Two Fraction which is recristalization was the higer than Î±-tokoferol and vitamin C